Long-range spatial variability in sediment associations and solid-phase speciation of antimony and arsenic in a mining-impacted river system. (December 2021) - Doherty, Steven; Tighe, Matthew K.; Milan, Luke A.; Johannessen, Bernt; Mitchell, Valerie; Hamilton, Jessica; Johnston, Scott G.; Wilson, Susan C.
Abstract: Solid-phase associations and speciation of antimony (Sb) and arsenic (As) were quantified in sediments (<2 mm) over the 320 km of metalloid dispersion in the mining impacted Macleay River, Australia, using a combination of sequential extractions and X-ray absorption spectroscopy (XAS). The aim of the work was to identify geochemical influences on metalloid availability as the elements dispersed through the river environments, and to compare and contrast the changes in metalloid association. Bioavailable fractions of As (2.2–7.7%) exceeded those of Sb (1.3–4.8%), however bioavailable Sb showed a positive correlation with downstream distance from the primary contamination zone while no such relationship was apparent for As. Amorphous-associations of both Sb (10–59%) and As (16–43%) increased significantly downstream. More than 50% of As occurred in residual phases at all sites (51–81%), but residual Sb was highly variable and localised (36–88%). Primary arsenopyrite was an important residual phase in upper catchment sediments but stibnite was not detected at these sites suggesting that dissolution and oxidation of the primary Sb sulfide occurred more rapidly. Metalloid associations showed the greatest contrast in the tidally-inundated and more redox active sites, where the increase in Sb in recalcitrant sediment phases suggested enhanced sequestration, whereas As predominantly remained in amorphous associations. XAS near-edge structure analysis revealed that pentavalent metalloid forms were dominant (49–98%) in the system, but up to 25% were in trivalent forms at tidally-inundated lower catchment sites. The contrasting Sb and As environmental geochemistry evident through the contaminated Macleay River, and the significant influence of prevailing geochemistry and fluvial processes on association and speciation, clearly demonstrates that risk can only be fully characterised by catchment wide understanding of contamination events. Highlights: Geomorphic location influenced Sb and As sediment species in a mine impacted river. Primary sulfide minerals were important for As but not Sb in the source zone. Sb(V) and As(V) were dominant, and amorphous associations increased downstream. Tidally-flooded sites showed trivalent species and an increase in recalcitrant Sb. As was more bioavailable, but bioavailable Sb fractions increased downstream.